1988
DOI: 10.1056/nejm198810063191404
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Findings in Autosomal Dominant Polycystic Kidney Disease

Abstract: Echocardiography, including Doppler analysis, was performed to assess the prevalence of cardiac abnormalities in 163 patients with autosomal dominant polycystic kidney disease, 130 unaffected family members, and 100 control subjects. In these three groups, the prevalence of mitral-valve prolapse was 26, 14, and 2 percent, respectively (P less than 0.0005). A higher prevalence of mitral incompetence (31, 14, and 9 percent, respectively; P less than 0.005), aortic incompetence (8, 3, and 1 percent, respectively;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
3
2

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(89 citation statements)
references
References 33 publications
5
79
3
2
Order By: Relevance
“…[27][28] AR can co-exist with other cardiac-specific anomalies such as mitral valve prolapse, mitral incompetence, tricuspid incompetence and tricuspid valve prolapse. [27][28] Intra-cerbral aneurysms (ICA): Dunger was the first to report the association between ADPKD and ICA in 1904. 29 Intra-cerebral aneurysms generally occur in 9-12% of ADPKD patients compared to 2-3% in the general population.…”
Section: Extra-renal Presentationsmentioning
confidence: 99%
“…[27][28] AR can co-exist with other cardiac-specific anomalies such as mitral valve prolapse, mitral incompetence, tricuspid incompetence and tricuspid valve prolapse. [27][28] Intra-cerbral aneurysms (ICA): Dunger was the first to report the association between ADPKD and ICA in 1904. 29 Intra-cerebral aneurysms generally occur in 9-12% of ADPKD patients compared to 2-3% in the general population.…”
Section: Extra-renal Presentationsmentioning
confidence: 99%
“…Vascular defects are also observed in Pkd1 hypomorphic mouse mutants (Kim et al, 2000;Hassane et al, 2007), where basement membrane thickening is the earliest pathology associated with dissecting aneurysm (Hassane et al, 2007). Other extra renal manifestations of ADPKD that may involve matrix structural defects include gastrointestinal cysts, cardiac valvular defects and pericardial effusion (Hossack et al, 1988;Qian et al, 2007). An altered ECM has long been known to be associated with ADPKD pathology in human tissue (Candiano et al, 1992;Somlo et al, 1993), and in ADPKD animal and cell culture models (Schafer et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Valvular heart disease occurs in approximately 18% of cases. Mitral valve billowing, prolapsed, and regurgitation are present in 5.3%, 2.6%, and 7.9% of cases, respectively (39). Although previous echocardiography studies indicated a high prevalence of left ventricular hypertrophy and increased left ventricular mass index in both normotensive and hypertensive ADPKD patients, recent cardiac MR imaging used in 541 ADPKD participants in the Halt Progression of Polycystic Kidney Disease trials (40) revealed a lower than expected prevalence of left ventricular hypertrophy with a frequency of 3.9%.…”
Section: Surgical Resectionmentioning
confidence: 99%